The Impact of Organizational Silence on a Sustainable Competitive Advantage: A Case Study of the Electrical Industries Company - Al-naqeeb, Muayad Abdulkareem Shakir; Ismael, Imad Khaleel (Mediterranean Journal of Social Sciences, 2021)
This study seeks to analyze the factors causing organizational silence and the impact of this on the sustainable competitive advantage of organizations, The researchers used the descriptive approach, being the best approach from the researchers' point of view, to clarify the relationship between the research variables and the achievement of the study objectives, The Electric Industries Company was chosen to understand the reality of organizational silence and analyze what is required in order to make the necessary recommendations that can contribute to sustaining the company's competitive advantage and reducing the phenomenon of organizational silence and its effects. The results of research confirmed the inverse correlation between organizational silence and the sustainable competitive advantage, also that the organizational silence has a negative effect on the sustainable competitive advantage. Received: 11 February 2021 / Accepted: 20 April 2021 / Published: 17 May 2021